2021
DOI: 10.1007/s10311-021-01351-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineered magnetic oxides nanoparticles as efficient sorbents for wastewater remediation: a review

Abstract: The rapid urbanization and industrialization is causing worldwide water pollution, calling for advanced cleaning methods. For instance, pollutant adsorption on magnetic oxides is efficient and very practical due to the easy separation from solutions by an magnetic field. Here we review the synthesis and performance of magnetic oxides such as iron oxides, spinel ferrites, and perovskite oxides for water remediation. We present structural, optical, and magnetic properties. Magnetic oxides are also promising phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 355 publications
(268 reference statements)
0
12
0
Order By: Relevance
“…The inconsistency in these results might be due to a particle size variance. It is well founded that the SPR bands are very susceptible and highly dependent on the nanoparticles size, shape, FeSO 4 ·7H 2 O concentration and the type of substrates presented in the biological extract [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inconsistency in these results might be due to a particle size variance. It is well founded that the SPR bands are very susceptible and highly dependent on the nanoparticles size, shape, FeSO 4 ·7H 2 O concentration and the type of substrates presented in the biological extract [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers reported the broad applicability of perovskite nanomaterials from catalysis to the adsorption process due to their excellent optical, magnetic, thermal, and electric characteristics. 8,9 The high adsorption capacity and fast kinetics of perovskites make them suitable adsorbent candidates in industrial wastewater bearing high levels of organic dyes. [10][11][12] For instance, Cuijin Pei et al 2016 showed a remarkable adsorption capacity (7154 mg g À1 in 40 min) for Acid Fuschia (AF) using a 3-dimensional hierarchical ZnO adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers reported that these perovskite nanomaterials could be used in many applications from catalysis to adsorption process due to good optical, magnetic, thermal, and electric characteristics. 8,9,14 Several synthetic methods have been reported for preparing perovskites that included sol-gel, Pechini, co-precipitation, chelating complex, and pyrolysis. [15][16][17][18] The perovskites exhibit not only higher adsorption capacity and fast kinetics but also act as suitable adsorbents toward industrial wastewater with high concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In water pollution control and wastewater management, the adsorption process is a promising method because it has design and operational simplicity, higher efficacy, lower maintenance, and no undesirable byproducts (de Andrade et al 2018 ; Wang et al 2022 ; Zare et al 2021 ; Maksoud et al 2022 ). The non-conventional adsorption approach based on molecularly imprinted polymers offers a valid technology for the selective removal of specific target pollutants in (waste)water treatment.…”
Section: Introductionmentioning
confidence: 99%